Collaborations of Russian Universities with BRICS Universities: Forms, Results, Opportunities - M. A. Lukashenko; E. V. Alekseeva; T. Yu. Dobrovolskaya; A. A. Shavyrina (Высшее образование в России, 2025)
The issues of effective interaction between Russian universities and universities of the BRICS countries are becoming increasingly important in practice and science today. Cooperation in education and science is one of the main areas of partnership announced at the BRICS forum. Including the maximum number of Russian universities in such a partnership will not only significantly increase the export of educational services, but will also lead to strategically important scientific results and the development of innovations through joint research. Hence the need to find effective forms and organizational solutions for educational collaboration for Russian universities.The purpose of this study is to present real and potential forms of collaboration between Russian universities and BRICS universities and to identify the actual results of their implementation using the example of the top ten Russian universities in the BRICS university ranking.The article presents the results of the study of the international activities of the universities in question based on self-study data and analysis of the content of the websites of these universities. The forms of cooperation between universities in the areas of educational, scientific and innovative activities, as well as within the framework of cultural and humanitarian cooperation programs, are identified and shown using examples. The article presents organizational solutions for the formation of educational collaborations: Network University, alliances formed as a result of agreements on interaction between two universities – Russian and a BRICS member country, consortiums uniting several universities to implement a specific project, as well as associations. The paper proposes the use of university co-opetition, in which universities join forces to achieve common goals while maintaining their competitive positions. This approach allows universities to pool resources, share expertise, and implement large-scale projects that would be difficult or impossible to implement alone. A case of collaboration between universities and businesses is presented using the example of Russia and Kazakhstan with the aim of transforming universities into entrepreneurial universities, and the possibility of using a similar model in interaction with universities in the BRICS countries is shown.An algorithm for forming a strategy for interaction between regional educational organizations and partner companies has been developed, and it has been shown that a modern strategy for developing international activities of a university can be based on solving the problems of large companies – industry leaders through university interaction.